Hydrogenation Reactions with Synergistic Catalysis of Pd single atoms and nanoparticles under Near‐Ambient Conditions. Issue 10 (4th January 2023) - Yang, Junxia; Yang, Li; Zhang, Ling; Yu, Tie; Zhai, Dong; Wang, Honglei; Zhou, Wei; Li, Yajuan; Ren, Guoqing; Sun, Lei; Deng, Weiqiao
Abstract: Due to the limited resources and high cost of noble metals, boosting their catalytic activities is highly desired in the current catalysis industry. Here, we report a synergetic catalyst, combining Pd 2+ and Pd 0 species in a nitrogen‐doped porous carbons (NPC), which shows boosted catalytic activities in hydrogenation reactions of organic nitro compounds (nitrobenzene, 4‐nitrophenol, 1‐nitronaphthalene and 1‐nitropropane) under near ambient conditions. This synergetic catalyst NPC‐[Pd] was synthesized by partial reduction of a palladium‐loaded NPC. The catalytic activities and selectivity of NPC‐[Pd] for hydrogenation were enhanced significantly compared with those of NPC‐Pd 2+ or NPC‐Pd 0 nanoparticles. Theoretical calculations show that H2 preferentially dissociates on Pd nanoparticles, and then organic molecules (nitrobenzene) can be captured and react with the dissociated H atom on Pd 2+ sites. Similar reaction procedure also occur on Pt or Rh. Hydrogenation of different aromatic compounds with different functional groups (naphthalene, 4‐nitrochlorobenzene, benzaldehyde and acetophenone) confirmed the broad excellent catalytic activity of this synergistic catalyst. Abstract : Synthesis of a synergistic catalyst of Pd single atoms and Pd nanoparticles is presented, which shows broad catalytic activity towards hydrogenation of organic nitro molecules and functional aromatics.